Relationship between anxiety and chronic orofacial pain of temporomandibular disorder in a group of university students - Monteiro, Douglas Roberto [UNESP]; Zuim, Paulo Renato Junqueira [UNESP]; Pesqueira, Aldieris Alves [UNESP]; Ribeiro, Paula do Prado [UNESP]; Garcia, Alício Rosalino [UNESP] (Japan Prosthodontic Society, 2011)
Purpose: This study evaluated the relationship between anxiety levels and severity degrees of chronic orofacial pain of temporomandibular disorder in brazilian university students. Methods: 150 volunteers (117 men and 33 women), with age ranging from 17 to 30 years, were subjects to this study. Spielberger's trait-state anxiety inventory was used to evaluate trait and state anxiety of the students, while examination for chronic orofacial pain was performed in accordance with the Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD). Association between anxiety levels and severity degrees of chronic orofacial pain was tested using the Chi-square test. The significance level was set at p<.05. Results: The results showed that 32.7% (n = 49) of the subjects exhibited TMD, and the intensity of chronic orofacial pain was classified as degree 1 in 85.7% (n = 42) and as degree 2 in 14.3% (n = 7) of them. Based on the results of the Spielberger's trait-state anxiety inventory, the majority of the students had moderate anxiety (48.6% and 48.1%, respectively). The correlation between trait-anxiety levels and chronic orofacial pain degrees was significant and positive (p<.05). However, no significant correlation was found to state-anxiety levels and chronic orofacial pain degrees (p>.05). Conclusion: It was concluded that chronic orofacial pain of TMD could be present in university students and anxiety may be related. © 2010 Japan Prosthodontic Society. Published by Elsevier Ireland. All rights reserved.
Keywords: Anxiety; Orofacial pain; TMD; adolescent; adult; anxiety; Brazil; chronic disease; face pain; female; human; male; pathophysiology; student; temporomandibular joint disorder; Adolescent; Adult; Chronic Disease; Facial Pain; Female; Humans; Male; Students; Temporomandibular Joint Disorders